Islam and Multiculturalism in Building Harmony in a Diverse Society - Defriza, Rita; Harahap, Sumper Mulia; Hidayat, Rahmad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This article explores the role of Islam in fostering social harmony within the diverse community of Nagajuang Subdistrict, Mandailing Natal Regency, where the population is predominantly non-Muslim. This research employs a qualitative method with a case study design and a descriptive-analytical approach. The study investigates social interactions between Muslims and Christians and identifies key factors that support peaceful coexistence. The research data were collected from the community of Nagajuang Subdistrict, Mandailing Natal Regency, North Sumatra, which represents a valuable case of interfaith harmony. The data consist of interview transcripts with religious leaders, traditional leaders, and community members; field notes from participatory observation of daily interactions; and textual data from local archives and reports on interfaith relations. These data were collected through purposive sampling based on the informants’ involvement in interreligious and community activities. Thematic analysis was employed, involving data reduction, categorization into themes such as harmony factors, challenges, and the role of Islam, followed by conclusion drawing. The findings reveal that Islamic values of moderation, such as rahmatan lil ‘alamin and wasatiyyah, are practiced to promote tolerance and unity. Local cultural traditions emphasizing mutual cooperation (gotong royong) further strengthen social bonds across religious lines. Despite this harmony, challenges like religious intolerance and socio-economic inequality persist. This study highlights the significance of combining Islamic values with local cultural wisdom to support multicultural coexistence. It offers practical recommendations for strengthening multicultural education and promoting collaboration among government bodies, religious institutions, and communities. Nagajuang serves as a model of successful interfaith harmony, contributing valuable insights into social integration in diverse societies.